TINGKAT KEPUASAN PETANI PADA KINERJA PENYULUH DALAM MELAKSANAKAN PROGRAM PENYULUHAN PERTANIAN DI DESA PARIS KECAMATAN MOOTILANGO - Rauf, Nurain; Bempah, Irwan; Saleh, Yanti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
The study aimed to determine the level of farmer satisfaction with the agricultural extension program in extension program in Paris Village. This research was conducted in Paris Village, Mootilango Subdistrict using a survey research type with information collection techniques carried out using a list of questions compiled in a questionnaire. This study had a sample of 39 respondents who used the Important Performance Analysis (IPA) analysis technique. Based on the results of this analysis, it is found that the performance of agricultural extension workers is good in carrying out extension activities on time and carrying out tasks according to their needs. Agricultural extension workers have good insight and communication skills so that farmers in Paris Village quickly understand the delivery provided by agricultural extension workers and extension workers can provide solutions to solving problems and work together in practicing farming activities, comply with each other in the agricultural system, have many ideas and offer innovations in guiding agricultural extension activities.